Bentuk dan Makna Budaya dalam Ungkapan Lagu-lagu Pop Melayu Manado (Suatu Kajian Linguistik Antropologi) - Egeten, Albert Jacob (Universitas Sam Ratulangi, 2016)
This research is an attempt to find the cultural meaning of the malay manadonese popular. The aim of this research are to 1) identify and classify the form of utterances in form of words, phrases, clauses, sentences, and discourse in the songs; 2) explain the cultural meaning in the form of words, phrases, clauses, sentences, and discourse in the songs. The method used in this research was descriptive qualitative. The data were collected by direct observation, document research and recording. There were two steps in data analysis 1) analyze the utterances and 2) anthropological linguistics analysis. The result showed that the manadonese malay popular song had the local cultural openess. Keywords:meaning, cultural, utterances